Cooperators overcome migration dilemma through synchronization - Shubhadeep Sadhukhan; Rohitashwa Chattopadhyay; Sagar Chakraborty (Physical Review Research, 2021)
Synchronization, cooperation, and chaos are ubiquitous phenomena in nature. In a population composed of many distinct groups of individuals playing the prisoner's dilemma game, there exists a migration dilemma: No cooperator would migrate to a group playing the prisoner's dilemma game lest it should be exploited by a defector; but unless the migration takes place, there is no chance of the entire population's cooperator fraction to increase. Employing a randomly rewired coupled map lattice of chaotic replicator maps, modeling replication-selection evolutionary game dynamics, we demonstrate that the cooperators—evolving in synchrony—overcome the migration dilemma to proliferate across the population when altruism is mildly incentivized making few of the demes play the leader game.